The politics of prison air: Breath, smell, and wind in Myanmar prisons. (October 2021) - Martin, Tomas Max
This article explores what air means and entails in penal settings and examines how carcerality attaches itself to air. With inspiration from social science approaches to the study of air, I propose that the lived experience of prison air can be fruitfully analyzed through the notions of breath, smell, and wind. This point is explored through two incidents about prison air drawn from ethnographic fieldwork in Myanmar. Together they illustrate a shift in Myanmar penality from a martial logic of destroying the enemy towards an internationally infused rationality of control and care. The first is a tale of an imprisoned engineer's subversive effort to improve the air quality in prisons; the second, the design and building of tuberculosis wards in prisons that aim to bring prison air in line with international standards. The analysis of these incidents broadens the analytical sensorium of prison air by drawing attention to, on the one hand, a basic empirical and affective sensing of air, recognising air as a scarce and coveted resource that prison actors' appropriate to survive. On the other hand, attention is drawn to the possibility of sensing with air, whereby the discourses, technologies, rules, and practices of air can be utilized as entry points for the analysis of prison governance and the transitional dynamics of penality.